2019
DOI: 10.3390/ijms20051248
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tumor Heterogeneity on Diagnostics and Novel Therapeutic Strategies in Multiple Myeloma

Abstract: Myeloma is characterized by extensive inter-patient genomic heterogeneity due to multiple different initiating events. A recent multi-region sequencing study demonstrated spatial differences, with progression events, such as TP53 mutations, frequently being restricted to focal lesions. In this review article, we describe the clinical impact of these two types of tumor heterogeneity. Target mutations are often dominant at one site but absent at other sites, which poses a significant challenge to personalized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 75 publications
1
45
0
2
Order By: Relevance
“…Asymptomatic plasma cell dyscrasias, such as monoclonal gammopathy of undetermined significance (MGUS) and smoldering MM, have a propensity to progress to symptomatic MM [19]. Cytogenetic analyses have shown that MM is a heterogenous disease, with two main primary chromosomal events: (i) hyperdiploid MM presents with several trisomies (chromosomes 3, 5, 7, 9, 11, 15, 19, and 21), and (ii) non-hyperdiploid MM is associated with primary Ig heavy-chain translocations, such as t(4;14), t (11;14), t(14;16), or t (14;20), which result in overexpression of specific oncogenes [20]. During further disease evolution, myeloma cells acquire secondary chromosomal aberrations, including (i) amplification of chromosome 1q, (ii) deletion of chromosome 1p, (iii) deletion of chromosome 17p, which includes the tumor-suppressor gene TP53, and (iv) translocations involving the MYC locus on chromosome [20][21][22].…”
Section: Targeting Cd38 In MMmentioning
confidence: 99%
See 2 more Smart Citations
“…Asymptomatic plasma cell dyscrasias, such as monoclonal gammopathy of undetermined significance (MGUS) and smoldering MM, have a propensity to progress to symptomatic MM [19]. Cytogenetic analyses have shown that MM is a heterogenous disease, with two main primary chromosomal events: (i) hyperdiploid MM presents with several trisomies (chromosomes 3, 5, 7, 9, 11, 15, 19, and 21), and (ii) non-hyperdiploid MM is associated with primary Ig heavy-chain translocations, such as t(4;14), t (11;14), t(14;16), or t (14;20), which result in overexpression of specific oncogenes [20]. During further disease evolution, myeloma cells acquire secondary chromosomal aberrations, including (i) amplification of chromosome 1q, (ii) deletion of chromosome 1p, (iii) deletion of chromosome 17p, which includes the tumor-suppressor gene TP53, and (iv) translocations involving the MYC locus on chromosome [20][21][22].…”
Section: Targeting Cd38 In MMmentioning
confidence: 99%
“…Cytogenetic analyses have shown that MM is a heterogenous disease, with two main primary chromosomal events: (i) hyperdiploid MM presents with several trisomies (chromosomes 3, 5, 7, 9, 11, 15, 19, and 21), and (ii) non-hyperdiploid MM is associated with primary Ig heavy-chain translocations, such as t(4;14), t (11;14), t(14;16), or t (14;20), which result in overexpression of specific oncogenes [20]. During further disease evolution, myeloma cells acquire secondary chromosomal aberrations, including (i) amplification of chromosome 1q, (ii) deletion of chromosome 1p, (iii) deletion of chromosome 17p, which includes the tumor-suppressor gene TP53, and (iv) translocations involving the MYC locus on chromosome [20][21][22]. The International Myeloma Working Group (IMWG) classifies the presence of del(17p) and/or t (4;14), and/or t(14;16) as high-risk cytogenetic markers associated with reduced survival of patients with MM [23].…”
Section: Targeting Cd38 In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably, this last question will be answered in the near future, thanks to the increasing use of anti-CD38 mAb combinations in early lines. These issues are particularly challenging considering the wide heterogeneity of myeloma cell populations [121]. Immunotherapy seems to be a potential strategy for targeting virtually all tumor subclones, as effector mechanisms rely on the patient immune system.…”
Section: Discussionmentioning
confidence: 99%
“…İlerleyen süreçte klonal plazma hücrelerinin edindiği yeni moleküler değişimler hastalığın tipik bulgularının gelişmesine (anemi, böbrek yetersizliği, litik kemik lezyonları ve patolojik kırıklar, hiperkalsemi, kemik iliği yetersizliği) yol açar. MM hematolojik kanserlerle ilişkili ölümlerin %20'sinden sorumludur (7,8). Son 10 yılda immünomodülatör ilaçlar, proteozom inhibitörleri ve yakın zamanda hedefe yönelik tedavilerin geliştirilmesi ile hastalıkta önemli sağkalım avantajı elde edildiği halde halen hastaların %15 kadarında hastalık kötü seyirli olmaktadır (9).…”
Section: Introductionunclassified